Time and ecological resilience: can diurnal animals compensate for climate change by shifting to nocturnal activity?. Issue 1 (12th November 2018) - Levy, Ofir; Dayan, Tamar; Porter, Warren P.; Kronfeld‐Schor, Noga
Abstract: Considerable research is aimed at developing predictions of ecosystem responses to climate change, focusing on the spatial scale, such as range shifts and contractions, as well as activity restrictions to shaded microhabitats. On the other hand, the ability of species to shift their activity times during the diel cycle, and consequently to alter the environment in which activity occurs, has been largely neglected. Daily activity patterns are perceived as fairly fixed; however, natural changes in activity patterns have been reported in increasing numbers of species. Here, we present a framework that explores how shifts in activity patterns may buffer impacts of climate change. To demonstrate our framework, we simulated costs of activity of diurnal and nocturnal rodents and showed that future summers may decrease the energetic demands of nocturnal mammals while increasing water demands of diurnal mammals. Climate projections suggest that vegetation cover and water availability will decrease under future climate scenarios, especially in areas where water demands are expected to increase the most. These changes are expected to limit the ability of diurnal animals to restrict activity to shaded microhabitats and to keep a positive water balance. Our analysis shows that by shifting to nocturnality, diurnal mammals may mitigate the high water costs of future summers. We suggest that future research should explore the role of the diel time axis as an ecological resource when predicting the impacts of climate change.